Infrarenal Aorta Thrombosis Associated with H1N1 Influenza A Virus Infection - Can Hüzmeli; Mustafa Saglam; Ali Arıkan; Barıs Doner; Gulay Akıncı; Ferhan Candan (Case Reports in Infectious Diseases)
Influenza viruses are members of the Orthomyxoviridae family, of which influenza A, B, and C viruses constitute three separate genera. Arterial thrombosis associated with H1N1 influenza A virus infection has rarely been reported. A Turkish man aged 28 years was admitted to our emergency department with dyspnea, bilateral lower extremity insensitivity, and cold. He reported symptoms of fever, myalgia, and cough, which he had had for fifteen days before being admitted to our hospital. The patient was tested for pandemic influenza A (H1N1) virus using polymerase chain reaction (PCR) tests, which were positive. Abdominal computerized tomography with contrast revealed a large occlusive thrombus within the infrarenal aorta.